Power and Energy Management with Battery Storage for a Hybrid Residential PV-Wind System – A Case Study for Denmark. (November 2018) - Stroe, Daniel-Ioan; Zaharof, Andreea; Iov, Florin
Abstract: The energy generation paradigm is shifting from centralized fossil-fuel-based generation to distributed-based renewable generation. Thus, hybrid residential energy systems based on wind turbines, PV panels and/or micro-turbines are gaining more and more terrain. Nevertheless, such a system needs to be coupled with an energy storage solution, most often a battery, in order to mitigate its power generation variability and to ensure a stable and reliable operation. In this work, two power and energy management strategies for a hybrid residential PV-wind system with battery energy storage were evaluated. Simple but customized performance models for PV modules and a small wind turbine have been developed; furthermore, the models have been parameterized based on real-life time-series for irradiance and wind speed, characteristic for a site in Denmark. The stress, to which the battery was subjected, while providing the two energy management strategies, was also quantified.